‘Telephone Triage’: a possible means of managing the after-hours patient load at primary health care facilities in South Africa - A. A. Adeniji; L. H. Mabuza (South African Family Practice)
The rate at which routine patients are using the emergency department (ED) as a path to enter into the healthcare system in South Africa’s community healthcare facilities and district hospitals is alarming. The increasing number of acutely presenting, less stable and routine patients are being left to the care of a reduced number of health carers after hours, at weekends and during public holidays. This circumstantial disproportionality forms the breeding ground for poor patient care, healthcare workers’ burnout and inappropriate use of referral pathways. Not all the patients occupying the ED waiting rooms actually need emergency care. A sizeable number of patients in the waiting line are routine cases that could wait without any undesirable clinical outcomes. This opinion paper looks into the use of telephones to control after-hours patient loads at primary health care facilities in South Africa.